Utilization of marine snails for the sustainable synthesis and crystallographic characterization of nano-crystallite hydroxyapatite - Md. Kawcher Alam; Md. Sahadat Hossain; Md. Anayet Ullah; Newaz Mohammed Bahadur; Samina Ahmed (Hybrid Advances)
In the present investigation, several biogenic sources of calcium were used to produce HAp nanomaterials by the use of a typical wet chemical precipitation technique. To determine the development of HAp nanocrystals, a variety of characterization methods were used, including X-ray diffraction (XRD), scanning electron microscopy (SEM), and Fourier transform infrared (FT-IR) spectroscopy. The results of XRD were used to evaluate a wide range of factors related to structure, such as lattice parameters, degree of crystallinity, dislocation density, microstrain, crystallinity index, and preference growth. The crystallite size of the produced HAp crystals was calculated using the equations of different models. Each of the formed HAp exhibits crystal arrangements that are within the allowed range of 1–150 nm, which the aforementioned models were used to figure out from the XRD information. Furthermore, the EDX examination (Ca, P, and O percentages) and Rietveld refinement (about 95 % HAp) verified the makeup of the resultant HAp particles.